2019
DOI: 10.1029/2018jc014334
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends in Phytoplankton Chlorophyll a and Size Structure in the Benguela Upwelling System

Abstract: The Benguela Upwelling System (BUS) is among the most productive ecosystems globally, supporting numerous fisheries and ecosystem services in Southern Africa. Sea‐viewing Wide Field‐of‐view Sensor and Moderate‐resolution Imaging Spectroradiometer‐Aqua chlorophyll a (Chla) concentrations between September 1997 and February 2018 were used to investigate long‐term trends in phytoplankton biomass and size structure (microphytoplankton [>20 μm], nanophytoplankton [2–20 μm], and picophytoplankton [<2 μm]) in the Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 121 publications
(274 reference statements)
1
24
0
Order By: Relevance
“…A tendency toward increasing upwelling in the SBUS was noted by several studies 22 24 in recent years. Conversely, Lamont et al 25 reported a decreasing trend in chlorophyll in the southern Benguela shelf region by season over the last 20 years.…”
Section: Introductionmentioning
confidence: 93%
“…A tendency toward increasing upwelling in the SBUS was noted by several studies 22 24 in recent years. Conversely, Lamont et al 25 reported a decreasing trend in chlorophyll in the southern Benguela shelf region by season over the last 20 years.…”
Section: Introductionmentioning
confidence: 93%
“…Yet, its strength could be weakened with the predicted decrease in upwelling intensity in the NBUS 47,48 . Whether the predicted enhancement in upwelling of the southern system 36,49 could however compensate for the lowered biological carbon pump efficiency of the NBUS, remains open for debate. Thus, in addition to the Southern Ocean, also a better understanding of the BUSs response to climate change is essential to predict the CO2 uptake efficiency of the biological carbon pump and the future evolution of CO2 in the atmosphere.…”
Section: Air-sea Co2 Flux Estimatesmentioning
confidence: 99%
“…This is also reflected in primary productivity which in the SBUS is twice as large in the summer than winter 61 . Furthermore, studies have shown a decrease and intensification of upwelling in the NBUS and SBUS, respectively, over the past decade in response to global warming 36,49 and a southward shift of the SAA 47 . The associated increase in sea water temperatures in the NBUS 62 could potentially be related to the prominent decrease in zooplankton size spectra in the BUS 63 .…”
Section: Study Regionmentioning
confidence: 99%
“…During the last two decades satellite data indicate no significant trends in productivity (Demarcq, 2009;Verheye et al, 2016;Lamont et al, 2019) but there is a tendency toward an intensification of upwelling in the SBUS (Sydeman et al, 2014;Tim et al, 2015;Wang et al, 2015;Lamont et al, 2018Lamont et al, , 2019. Associated with this trend are shifts in the ecosystem structure such as an overall decrease in zooplankton abundance and a shift from large to smaller zoo-and phytoplankton species (Hutchings et al, 2012;Jarre et al, 2015;Verheye et al, 2016;Lamont et al, 2019).…”
Section: Study Areamentioning
confidence: 99%